Analysis of E-Bupot System Implementation on Taxpayer Satisfaction - heni pujiastuti; Sechan Bawazier (Management Research Studies Journal, 2021)
This study aims to examine the application of the e-Bupot system in tax transactions carried out by taxpayers. This study uses measurements, one of which is the effectiveness of a system that is tailored to the needs of users in supporting a business process, including information presented in the right time, in the right format so that it is easy to understand and consistent with the specified format. Indicators of the effectiveness of technology-based information systems are data security indicators, time indicators related to the speed and accuracy of information, accuracy indicators related to the level of freedom from error in information output, reports or output variations indicators related to the completeness of information content and relevance indicators showing the benefits generated from the product or output information. The test in this study used 40 respondents obtained by purposive random sampling in a KPP Pratama. In the test using the F-Test and T-Test through the SPSS program. Based on the test results, it is obtained that taxpayers get satisfaction in implementing the e-Bupot system but financially it does not provide significant benefits.